New Developments in Ostrowski's Type Inequalities by Using 13-Step Quadratic Kernel - Muawwaz, Muhammad; Maaz, Muhammad; Qayyum, Ather; Suzlin Supadi, Siti; Ali, Usman; Danial Faiz, Muhammad (Malaysian Journal of Science (MJS), 2025)
The Ostrowski inequality has recently been widely recognized as a powerful mathematical tool for modeling and analysing many physical and real-world events. This inequality has been applied across diverse mathematical fields, including complex analysis, numerical analysis, functional analysis, and stochastic analysis. The purpose of this paper is to develop Ostrowski's type integral inequalities by using a special type of 13-steps quadratic kernel. The incorporation of this new kernel gives some new error bounds for various quadrature rules. Applications for cumulative distributive functions are also discussed.